The gender education gap in China: the power of water - Yasheng Maimaiti; William Stanley Siebert (Institute for the Study of Labor (IZA), 2009)
We investigate girls' school dropout rates, bringing forward a novel variable: access to water. We hypothesise that a girl's education suffers when her greater water need for female hygiene purposes after menarche is not met because her household has poor access to water. For testing we use data from rural villages in the China Health and Nutrition Survey. We find that menarche is associated with an increase in the school dropout rate, and indeed the effect is weaker for girls who have good access to water. Water engineering can thus contribute significantly to reducing gender education gaps in rural areas.
urn:nbn:de:101:1-2009051354
Keywords: I21; J16; O15; L95; Q25; 330; Education; gender gaps; menarche; water; China; Frauenbildung; Geschlechterdiskriminierung; Hygiene; Wasserversorgung; Ländlicher Raum; China